OP007 Detection of mucosal healing with a serum marker panel in adalimumab-treated patients with ulcerative colitis. (16th January 2018) - de Bruyn, M; Ringold, R; Martens, E; Ferrante, M; Van Assche, G; Opdenakker, G; Dukler, A; Vermeire, S
Abstract: Background: Surrogate markers that accurately detect mucosal healing (MH) in patients with ulcerative colitis (UC) are urgently needed. After infliximab therapy, neutrophil gelatinase B-associated lipocalin in complex with matrix metalloproteinase-9 (NGAL-MMP-9), cathelicidin LL-37 and chitinase 3-like 1 (CHI3L1), together with C-reactive protein (CRP) and neutrophil count were significantly associated with MH. We investigated whether these five markers were also associated with MH after treatment with adalimumab (ADM). Methods: Serum samples were obtained from 31 UC patients (58% female, median age 35.6 years) both at baseline and after a median (IQR) of 14 (10–25) weeks. All patients had endoscopic disease activity prior to treatment (Mayo endoscopic subscore/MES ≥2) and MH was defined at follow-up endoscopy as MES ≤1. NGAL-MMP-9, LL-37, and CHI3L1 were measured with ELISA. Binary logistic regression analysis was used to combine multiple markers. ROC analysis was used to test the performance of individual and combined markers. Non-parametric tests were performed, and p -values of <0.05 were considered significant. Results: Twenty-one patients (68%) achieved MH with ADM therapy. Compared with baseline, NGAL-MMP-9 levels significantly decreased in patients with MH (96.9 vs. 214.1 ng/ml, p = 0.002), whereas patients without MH had similar levels. Neutrophil count was significantly lower after ADM compared with baseline in patients with MH only (3.6 vs. 6.5 109/l, p = 0.023). CRP levels significantly decreased after ADM in patients with MH (15 to 1.1 mg/l, p = 0.008) and were higher at baseline in patients with MH compared with without MH (15 vs. 2.4 mg/l, p = 0.004). LL-37 levels significantly increased in patients without MH post-ADM compared with baseline (29 vs. 19.3 ng/ml, p = 0.034) and were significantly higher compared with patients with MH post-ADM (29 vs. 18.7 ng/ml, p = 0.031). CHI3L1 levels significantly decreased after ADM in patients with MH only (47.4 to 21.6 pg/ml, p = 0.049). The performance of NGAL-MMP-9 (AUC=0.70), neutrophil count (AUC=0.58), CRP (AUC=0.56), LL-37 (AUC=0.79), and CHI3L1 (AUC=0.69) to discriminate MH post-ADM significantly increased when all markers were combined (AUC=0.86). The 5-marker panel was discriminative for MH with 75% sensitivity, 89% specificity, 67% positive predictive value, and 92% negative predictive value. Conclusions: Neutrophil-related markers (NGAL-MMP-9, LL-37, and CHI3L1) as well as CRP and neutrophil count were significantly associated with MH after treatment with ADM. These data are in concordance with our previous findings in infliximab-treated patients. We therefore suggest a broad clinical utility of this panel for monitoring MH in UC patients under anti-TNF treatment.